Nickel roughening process of lead frame
By using nickel sulfamate, boric acid and additives to regulate nickel ion deposition in the lead frame nickel roughening process, a high-roughness nickel layer is formed, which solves the problem of copper substrate processing in the prior art and improves packaging reliability and environmentally friendly, simplifying process flow and reducing costs.
Patent Information
- Application Number
- CN202411258421.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing lead frame nickel roughening process requires additional treatment of the copper substrate, which increases production difficulty and cost, and may lead to high-active high-surface copper corrosion, affecting the quality of electroplating and environmental protection.
Using nickel sulfamate, boric acid and additives (such as nickel lateral deposition inhibitors and sodium dodecyl sulfate) in the electroplating nickel roughening solution, the high-roughness nickel layer is directly formed by regulating the deposition behavior of nickel ions, reducing the Cathodic polarization promotes the growth of nickel crystal nuclei, forms large-sized particles close to spherical shapes, improves surface roughness, simplifies process flow and reduces costs.
It realizes the direct formation of a high-rough nickel layer without the need for copper substrate treatment, improves the contact area between the lead frame and the packaging resin, enhances the reliability of chip packaging, reduces production costs, and reduces wastewater Emissions, achieve the goal of green and environmental protection.
Smart Images

Figure CN119121334A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lead frame roughening, and in particular to a nickel roughening process for a lead frame. Background Art
[0002] Human society has been developing in the information age for half a century and is beginning to face the advent of the intelligent age. 5G communications, artificial intelligence, smart driving, smart homes and other fields are beginning to flourish. This requires electronic products to be intelligent and interconnected, and puts forward higher performance requirements for chips that integrate a large number of electronic components and circuits, which has an impact on the chip design, manufacturing, packaging and testing industry. In the chip packaging and testing link, the chip packaging device must not only have sufficiently high electrical performance, but also have a long service life.
[0003] In the manufacture and use of packaged components, moisture in the air is an important cause of component damage or shortened life. When a packaged component absorbs too much moisture from the air, the moisture inside the component absorbs the heat generated by the chip, vaporizes and expands rapidly, exerting great pressure on the epoxy resin used for packaging, and eventually causing the packaged component structure to crack. The main way the industry increases the service life of packaged components is to extend the path of moisture in the air invading the component, increase the contact area between the chip carrier - the lead frame and the epoxy resin, and delay moisture intrusion and cracking of the component structure.
[0004] In lead frame design, grooves, glue locking holes, plum blossom points and other structures are usually used to increase the contact area between the lead frame and epoxy resin, form mechanical interlocking, and reduce moisture intrusion. In lead frame surface treatment, the industry usually adopts a roughening process - using surface treatment technology to increase the surface roughness of the lead frame, increase the contact area between the lead frame and epoxy resin, improve the bonding strength between the two, and improve the reliability of the packaged components.
[0005] Since the copper etching process has been developed to maturity, the research on the roughening process usually becomes a modification of the etching process, that is, adding additives to the mature copper etching formula to achieve micro-etching of the copper surface in order to obtain a rough copper surface. For lead frames such as full nickel-palladium-gold plated, the roughening process actually becomes a pre-treatment stage of the lead frame electroplating production, which increases the complexity of the lead frame electroplating manufacturing and brings additional production difficulty and cost; and electroplating other metal coatings on the roughened copper surface will cause the surface roughness to decrease, which will reversely put forward higher requirements for the roughening effect of the roughening process, further increasing the production cost and difficulty.
[0006] At the same time, copper itself has a high reactivity. After the surface area is increased by roughening, it will be easier to react chemically with substances in the production environment or equipment, causing corrosion or poor appearance of the roughened copper surface, resulting in the yield rate of subsequent electroplating production, and increasing the overall difficulty of lead frame electroplating manufacturing. Similar to etching solution, the roughening solution micro-etches the lead frame, and the copper content will continue to rise, continuously generating high-concentration copper-containing wastewater, increasing the pressure of wastewater treatment.
[0007] Therefore, a roughening process for other electroplated metals in lead frame manufacturing is needed to reduce the pre-process of electroplating manufacturing and avoid excessively high additional manufacturing costs. Summary of the invention
[0008] The purpose of the present application is to provide a nickel roughening process for a lead frame in view of the deficiencies of the current technology, and the nickel roughening process can directly obtain a rough nickel layer without the need to process the copper substrate, that is, no additional electroplating pre-treatment is required. The nickel roughening process significantly affects the crystallization of nickel ions on the surface of the lead frame during the electroplating nickel deposition process through the additives in the electroplating nickel roughening solution, reduces the limiting current density of the electroplating nickel roughening solution, inhibits the deposition in the high current density area, and forms rounded grains close to spherical. At the same time, it also has the advantages of accelerating the process of nickel ion electron deposition, reducing cathode polarization, promoting the growth of nickel crystal nuclei rather than nucleation, forming larger-sized particles, improving surface roughness, and finally forming an electroplated rough nickel layer with a certain roughness, which will not cause the nickel metal content in the electroplating nickel roughening solution to continue to rise, reducing wastewater discharge, and being green and environmentally friendly.
[0009] The present application provides a nickel roughening process for a lead frame, which adopts the following technical solution: A nickel roughening process for a lead frame comprises the following steps: degreasing→pickling→electroplating nickel roughening→pickling, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, and the electroplating nickel roughening solution comprises the following components: 90-130 g / L of nickel sulfamate, 40-50 g / L of boric acid, and 0.1-0.3 g / L of an additive.
[0010] By adopting the above technical scheme, nickel sulfamate: as the main nickel source, nickel ions are provided for electrodeposition. Its concentration directly affects the nickel content and deposition rate in the plating layer. Boric acid: as a buffer, it is used to stabilize the pH value of the plating solution to avoid the quality and deposition rate of the nickel layer affected by pH fluctuations. The additive has the ability to selectively adsorb on the surface of the lead frame, accelerate the process of nickel ion electron deposition, reduce cathode polarization, promote the growth of nickel crystal nuclei rather than nucleation, form larger particles, improve the surface roughness, and finally form a rough electroplated nickel layer with a certain roughness. At the same time, it also has the function of inhibiting the nucleation of nickel ion high current density areas, which is conducive to the growth of nickel crystal nuclei, forming rounded nickel grains close to spherical large sizes, and obtaining a rough electroplated nickel layer with high roughness. In short, by regulating the deposition behavior of nickel ions, a nickel layer with high roughness and good crystal morphology is formed. The obtained rough electroplated nickel layer not only increases the contact area between the functional area of the lead frame and the encapsulation resin, enhances the reliability of chip packaging, but also simplifies the production process, reduces production costs, and achieves the goal of green and environmentally friendly production.
[0011] Preferably, the additive consists of nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:5-6.
[0012] By adopting the above technical scheme, the nickel lateral deposition inhibitor has the selective adsorption on the surface of the lead frame, accelerates the process of nickel ion electron deposition, reduces cathode polarization, promotes the growth of nickel nuclei rather than nucleation, forms larger particles, improves surface roughness and finally forms a rough electroplated nickel layer with a certain roughness. Sodium dodecyl sulfate can reduce the surface tension of the plating solution, improve the wettability of the plating solution, can work synergistically with the nickel lateral deposition inhibitor, inhibit the nucleation of nickel ion high current density area, is conducive to the growth of nickel nuclei, forms rounded nickel grains close to spherical large size, and obtains a rough electroplated nickel layer with high roughness. Through the effect of the above additives, the nickel coarsening process of the present application can directly obtain a rough nickel layer without the need to process the copper substrate, reduces the process flow, and avoids additional production costs. At the same time, the process can also increase the contact area between the lead frame functional area and the encapsulation resin, and improve the reliability of chip packaging. In addition, the nickel coarsening process of the present application will not appear in the production process with high active high surface area copper surface, reducing the difficulty of lead frame electroplating production.
[0013] Preferably, the nickel lateral deposition inhibitor is composed of 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid in a mass ratio of 1:2.
[0014] By adopting the above technical scheme, 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid are used as nickel lateral deposition inhibitors, and their main function is to inhibit the deposition of nickel ions in the high current density area during the electroplating process, thereby affecting the growth mode of the grains. This selective deposition control can lead to the formation of larger particles, improve the surface roughness, and ultimately form a rough electroplated nickel layer with a certain roughness. There is a synergistic effect between 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid, as follows: Selective adsorption: 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid can both selectively adsorb on the surface of the lead frame, which helps to accelerate the deposition process of nickel ions gaining electrons, reduce cathode polarization, and promote the growth of nickel nuclei rather than nucleation. Grain growth control: Through synergistic action, the two inhibitors jointly inhibit the nucleation of the high current density area, which is conducive to the formation of large and round nickel grains, which is a key factor in obtaining a high roughness electroplated rough nickel layer. Improved wettability: Although sodium dodecyl sulfate is mainly responsible for reducing the surface tension of the plating solution and improving wettability, the presence of 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid also contributes to the overall performance of the plating solution, ensuring the uniformity and efficiency of the electroplating process. In summary, the synergistic effect of 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid not only optimizes the deposition behavior of nickel ions, but also promotes the formation of a rough electroplated nickel layer with high roughness, large particles and rounded grains, which is crucial to improving the reliability of chip packaging.
[0015] Preferably, the process conditions of the electroplating method are: the electroplating nickel roughening solution is 55-65°C, the cathode current density is 5-10A / dm2, the pH is 3.5-4.3, and the electroplating time is 60-120s.
[0016] Preferably, when the thickness of the electroplated rough nickel layer is 1 micrometer, the surface area of the electroplated rough nickel layer is 1.3-1.5 times the surface area of the corresponding electroplated region of the lead frame.
[0017] Preferably, the anode in the electroplating tank is a titanium alloy anode basket filled with sulfur-containing nickel blocks.
[0018] By adopting the above technical solution, during the nickel deposition process, sulfur ions will dissolve into the plating solution together with nickel, and the sulfur ions play a role in inhibiting the lateral growth of nickel, and assist the additive in obtaining a rough electroplated nickel layer with high roughness. The sulfur-nickel block serves as an anode, and its role is to supplement nickel ions during the electroplating process. The sulfur-nickel block releases sulfur ions during the nickel deposition process, and these sulfur ions dissolve into the plating solution together with nickel ions. The role of sulfur ions is to inhibit the lateral growth of nickel, that is, to inhibit the growth of nickel grains in the lateral direction. This can make the nickel grains more rounded and close to spherical, thereby improving the surface roughness of the electroplated rough nickel layer.
[0019] Preferably, the electroplating nickel roughening solution further comprises: TiO2 / SiO 2 Nanocomposite particles 5-10g / L, dispersant 0.3-0.5g / L.
[0020] Preferably, the TiO 2 / SiO 2 The method for preparing nanocomposite particles comprises the following steps: S81, according to the mass fraction, 5 parts of nano-TiO 2 The powder was added to a solution consisting of 500 parts of anhydrous ethanol and 300 parts of deionized water, and after being stirred evenly, 0.2 parts of polyvinyl pyrrolidone K30 was added, and ultrasonic dispersion was performed for 50-60 minutes to obtain a mixed solution A; S82, dripping 100 parts of 40% tetraethyl orthosilicate anhydrous ethanol solution into mixed solution A, and completing the dripping within 3 hours. During the dripping process, adding ammonia water every 20 minutes, adjusting the pH to 10-10.5, and continuing the reaction for 5-6 hours after the dripping is completed to obtain mixed solution B; S83, centrifuge the mixed solution B, wash it with pure water for 5 times, dry it in an oven at 120-130°C for 8-10 hours, grind it, and obtain TiO 2 / SiO 2 Nanocomposite particles.
[0021] By adopting the above technical scheme, the TiO 2 / SiO 2 Nanocomposite particles have spherical particles of 20 nanometers, small size, and nano effect. When added to the electroplating nickel roughening solution, they are deposited together with nickel ions during the electroplating deposition process to obtain an ideal electroplating rough nickel layer with high roughness. 2 / SiO 2 Nanocomposite particles have a nano effect. When added to the electroplating nickel roughening solution, they are deposited together with nickel ions during the electroplating deposition process to obtain an ideal electroplating rough nickel layer with high roughness. 2 / SiO 2 The nanocomposite particles are deposited together with nickel ions during the electroplating deposition process, which helps to form larger particles and promotes the growth of nickel crystal nuclei rather than nucleation, and finally forms an electroplated rough nickel layer with a certain roughness. 2 / SiO 2 The nanocomposite particles work synergistically with other components such as additives and sulfur-nickel anode to promote the growth of nickel nuclei, inhibit the deposition in the high current density area, form rounded grains close to spherical, and obtain a rough electroplated nickel layer with high roughness. 2 / SiO 2The nanocomposite particles play a key role in improving the surface roughness and promoting the nucleation and growth of nickel crystal nuclei in the lead frame nickel roughening process of the present application.
[0022] Preferably, the nano-TiO 2 The average particle size of the powder is 5 nanometers.
[0023] Preferably, the dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3.
[0024] By adopting the above technical solution, the role of the dispersant in the nickel electroplating roughening solution is to increase the TiO 2 / SiO 2 The uniform distribution and suspension of nanocomposite particles prevents them from settling to the bottom of the electroplating tank. Sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether are three substances that form a dispersant in a mass ratio of 3:4:3. The synergistic effect between them is manifested in the following aspects: Sodium dodecylbenzene sulfonate has good surface activity and emulsification properties, which can reduce the surface tension of the liquid and make TiO 2 / SiO 2 Nanocomposite particles are more easily dispersed in the electroplating nickel roughening solution. Sodium dodecyl polyoxyethylene ether sulfate has good wettability and permeability, which can promote the 2 / SiO 2 The wetting and penetration of nanocomposite particles in the electroplating nickel roughening solution improves their dispersibility. Polyethylene glycol octylphenyl ether has good hydrophilicity and lipophilicity and can be used on TiO 2 / SiO 2 A protective film is formed on the surface of the nanocomposite particles to prevent them from agglomerating and settling. In summary, these three substances work together to improve the performance of TiO 2 / SiO 2 The dispersibility and stability of the nanocomposite particles in the electroplating nickel roughening solution are conducive to obtaining an electroplating rough nickel layer with uniform distribution and high roughness.
[0025] In summary, the beneficial technical effects of this application are: 1. Increasing the contact area between the lead frame functional area and the packaging resin is beneficial to improving the reliability of chip packaging.
[0026] 2. The nickel roughening process of the present application eliminates the need for pre-copper plating and conventional roughening processes on the lead frame.
[0027] 3. Highly active high surface area copper surfaces will not appear during the production process, reducing the difficulty of lead frame electroplating production.
[0028] 4. A rough electroplated nickel layer with a high specific surface area is directly formed by electroplating, and no additional treatment of the rough electroplated nickel layer is required, which reduces the process flow and avoids additional production costs.
[0029] 5. The additive is selectively adsorbed on the surface of the lead frame, which accelerates the process of electron deposition of nickel ions, reduces cathode polarization, promotes the growth of nickel crystal nuclei rather than nucleation, forms larger particles, increases surface roughness, and finally forms a rough electroplated nickel layer with a certain roughness.
[0030] 6. Preparation of TiO 2 / SiO 2 The nanocomposite particles are spherical particles of 20 nanometers, small in size, and have a nano effect. When added to the electroplating nickel roughening solution, they are deposited together with nickel ions during the electroplating deposition process to obtain an ideal electroplating rough nickel layer with high roughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 This is a SEM image of the electroplated rough nickel layer of the lead frame prepared in Example 3 of the present application. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] In the following embodiments, the degreasing process and pickling process are as follows: Oil removal process: ultrasonic oil removal is adopted, and the oil removal liquid includes the following components: sodium carbonate 25g / L, sodium hydroxide 25g / L, dimeroxy octylphenol ether 0.2g / L, triethanolamine 0.3g / L, temperature 50°C, oil removal time 3 minutes.
[0034] Pickling process: Pickling solution: 5 g / L pure sulfuric acid with a density of 1.84 g / mL, room temperature, time 30 s.
[0035] Preparation Example 1TiO 2 / SiO 2 Preparation of nanocomposite particles TiO 2 / SiO 2 The method for preparing nanocomposite particles comprises the following steps: S81, according to the mass fraction, 5g of nano-TiO 2 The powder was added to a solution consisting of 500 g of anhydrous ethanol and 300 g of deionized water, and after being stirred evenly, 0.2 g of polyvinyl pyrrolidone K30 was added, and ultrasonic dispersion was performed for 55 min to obtain a mixed solution A; S82, dripping 100 g of 40% tetraethyl orthosilicate anhydrous ethanol solution into mixed solution A, and completing the dripping within 3 hours. During the dripping process, adding ammonia water every 20 minutes, adjusting the pH to 10.3, and continuing the reaction for 5.5 hours after the dripping is completed to obtain mixed solution B; S83, centrifuge the mixed solution B, wash it with pure water for 5 times, dry it in an oven at 125°C for 9 hours, grind it, and obtain TiO 2 / SiO 2 Nanocomposite particles.
[0036] Example 1 A nickel roughening process for a lead frame comprises the following steps: degreasing → 2 water washings → pickling → 2 water washings → electroplating roughening → 2 water washings → pickling → 2 water washings → drying, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, the anode in the electroplating tank is a titanium alloy anode basket loaded with a sulfur-containing nickel block, the electroplating nickel roughening solution comprises the following components: 90 g / L nickel sulfamate, 40 g / L boric acid, and 0.1 g / L additive, the additive comprises a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:5, the nickel lateral deposition inhibitor comprises 2-imino-4-sulfurized biuret and diaminobenzene disulfonic acid in a mass ratio of 1:2, and the electroplating process conditions are: the electroplating nickel roughening solution is 55° C., the cathode current density is 5 A / dm 2 , pH 4.3, and electroplating time was 120 s.
[0037] Example 2 A nickel roughening process for a lead frame comprises the following steps: degreasing → 2 water washings → pickling → 2 water washings → electroplating roughening → 2 water washings → pickling → 2 water washings → drying, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, the anode in the electroplating tank is a titanium alloy anode basket loaded with a sulfur-containing nickel block, the electroplating nickel roughening solution comprises the following components: 130 g / L nickel sulfamate, 50 g / L boric acid, and 0.3 g / L additive, the additive comprises a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:6, the nickel lateral deposition inhibitor comprises 2-imino-4-sulfurized biuret and diaminodiphenylethylene disulfonic acid in a mass ratio of 1:2, and the electroplating process conditions are: the electroplating nickel roughening solution is 65°C, the cathode current density is 10 A / dm2 , pH 3.5, and electroplating time was 60s.
[0038] Example 3 A nickel roughening process for a lead frame comprises the following steps: degreasing → 2 water washings → pickling → 2 water washings → electroplating roughening → 2 water washings → pickling → 2 water washings → drying, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, the anode in the electroplating tank is a titanium alloy anode basket loaded with a sulfur-containing nickel block, the electroplating nickel roughening solution comprises the following components: 110 g / L nickel sulfamate, 45 g / L boric acid, and 0.2 g / L additive, the additive comprises a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:5.5, the nickel lateral deposition inhibitor comprises 2-imino-4-sulfurized biuret and diaminodiphenylethylene disulfonic acid in a mass ratio of 1:2, and the electroplating process conditions are: the electroplating nickel roughening solution is 60°C, the cathode current density is 7A / dm 2 , pH 3.9, and electroplating time was 90s.
[0039] Electroplating nickel roughening solution also includes: TiO 2 / SiO 2 5-10 g / L of nanocomposite particles and 0.3-0.5 g / L of a dispersant, wherein the dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3.
[0040] Comparative Example 1 The same as Example 3, except that the nickel lateral deposition inhibitor is 2-imino-4-sulfurized biuret.
[0041] Comparative Example 2 The same as Example 3, except that the nickel lateral deposition inhibitor is diaminostilbene disulfonic acid.
[0042] Example 4 A nickel roughening process for a lead frame, comprising the following steps: degreasing → 2 water washing → pickling → 2 water washing → electroplating roughening → 2 water washing → pickling → 2 water washing → drying, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, the anode in the electroplating tank is a titanium alloy anode basket loaded with a sulfur-containing nickel block, and the electroplating nickel roughening solution comprises the following components: 90 g / L nickel sulfamate, 40 g / L boric acid, 0.1 g / L additive, TiO 2 / SiO 25 g / L of nanocomposite particles and 0.3 g / L of dispersant, wherein the additive is composed of a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:5, the nickel lateral deposition inhibitor is composed of 2-imino-4-sulfurized biuret and diaminobenzene disulfonic acid in a mass ratio of 1:2, the dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3, and the electroplating process conditions are: the electroplating nickel roughening solution is 55°C, the cathode current density is 5A / dm 2 , pH 4.3, and electroplating time was 120 s.
[0043] Example 5 A nickel roughening process for a lead frame, comprising the following steps: degreasing → 2 water washings → pickling → 2 water washings → electroplating roughening → 2 water washings → pickling → 2 water washings → drying, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, the anode in the electroplating tank is a titanium alloy anode basket loaded with a sulfur-containing nickel block, and the electroplating nickel roughening solution comprises the following components: 130 g / L nickel sulfamate, 50 g / L boric acid, 0.3 g / L additive, TiO 2 / SiO 2 The nanocomposite particles are 10 g / L and the dispersant is 0.5 g / L. The additive is composed of a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:6. The nickel lateral deposition inhibitor is composed of 2-imino-4-sulfurized biuret and diaminobenzene disulfonic acid in a mass ratio of 1:2. The dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3. The electroplating process conditions are: the electroplating nickel roughening solution is 65°C, the cathode current density is 10 A / dm 2 , pH 3.5, and electroplating time was 60s.
[0044] Example 6 A nickel roughening process for a lead frame, comprising the following steps: degreasing → 2 water washing → pickling → 2 water washing → electroplating roughening → 2 water washing → pickling → 2 water washing → drying, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, the anode in the electroplating tank is a titanium alloy anode basket loaded with a sulfur-containing nickel block, and the electroplating nickel roughening solution comprises the following components: 110 g / L nickel sulfamate, 45 g / L boric acid, 0.2 g / L additive, TiO 2 / SiO 27 g / L of nanocomposite particles and 0.4 g / L of dispersant, wherein the additive is composed of a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:5.5, the nickel lateral deposition inhibitor is composed of 2-imino-4-sulfurized biuret and diaminobenzene disulfonic acid in a mass ratio of 1:2, the dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3, and the electroplating process conditions are: the electroplating nickel roughening solution is 60°C, the cathode current density is 7 A / dm 2 , pH 3.9, and electroplating time was 90s.
[0045] Comparative Example 3 The same as Example 6, except that the dispersant is sodium dodecylbenzene sulfonate.
[0046] Comparative Example 4 The same as Example 6, except that the dispersant is sodium dodecyl polyoxyethylene ether sulfate.
[0047] Comparative Example 5 The same as Example 6, except that the dispersant is polyethylene glycol octylphenyl ether.
[0048] Performance Testing The nickel-roughened lead frames prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were subjected to the following performance tests, respectively. The test results are shown in Table 1.
[0049] Roughness: The surface roughness Ra, Rz and RSm values were obtained by 3D laser microscope testing; Surface area multiple: the ratio of the surface area of the electroplated rough nickel layer to the surface area of the corresponding lead frame electroplated. The surface area of the electroplated rough nickel layer is tested by scanning electron microscopy (SEM) on the surface of the electroplated rough nickel layer of the lead frame.
[0050] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The nickel-roughened lead frame prepared in Example 1 to Example 3 has a surface area increased by more than 35% after being roughened by nickel electroplating, and the contact area with the epoxy resin is significantly increased, thereby improving the bonding strength and reliability of the package.
[0051] 2) The nickel-roughened lead frames prepared in Examples 4 to 6 have a surface area increased by more than 140% after being roughened by nickel electroplating, and the contact area with the epoxy resin is significantly increased, thereby improving the bonding strength and reliability of the package.
[0052] 3) The comparative analysis of the performance of the nickel roughened lead frame prepared by Example 3 and Comparative Examples 1-2 shows that the nickel lateral deposition inhibitor is composed of 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid in a mass ratio of 1:2. The synergistic effect between 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid not only optimizes the deposition behavior of nickel ions, but also promotes the formation of an electroplated rough nickel layer with high roughness, large particles and rounded grains, which is crucial to improving the reliability of chip packaging.
[0053] 4) The performance comparison analysis of the nickel roughened lead frame prepared in Example 6 and Comparative Examples 3-5 shows that the dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3, and the synergistic effect between them is used to jointly improve the TiO 2 / SiO 2 The dispersibility and stability of the nanocomposite particles in the electroplating nickel roughening solution are conducive to obtaining an electroplating rough nickel layer with uniform distribution and high roughness.
[0054] Figure 1 This is a SEM image of the electroplated rough nickel layer of the lead frame prepared in Example 3 of the present application. Figure 1 ,It can be seen that the nickel grains in the electroplated rough nickel layer are ,rounded grains close to spherical shapes, and the surface roughness is high, and the distribution is ,very uniform.
[0055] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A nickel roughening process for a lead frame, characterized in that: The method comprises the following steps: degreasing→pickling→electroplating nickel roughening→pickling, wherein the electroplating nickel roughening refers to obtaining an electroplated rough nickel layer by electroplating in an electroplating tank loaded with an electroplating nickel roughening solution, and the electroplating nickel roughening solution comprises the following components: 90-130 g / L nickel sulfamate, 40-50 g / L boric acid, and 0.1-0.3 g / L additives.
2. A nickel roughening process for a lead frame according to claim 1, characterized in that: The additive consists of a nickel lateral deposition inhibitor and sodium dodecyl sulfate in a mass ratio of 3:5-6.
3. The nickel roughening process for a lead frame according to claim 1, characterized in that: The nickel lateral deposition inhibitor is composed of 2-imino-4-sulfurized biuret and diaminostilbene disulfonic acid in a mass ratio of 1:
2.
4. The nickel roughening process for a lead frame according to claim 1, characterized in that: The process conditions of the electroplating method are: the electroplating nickel roughening solution is 55-65°C, the cathode current density is 5-10A / dm 2 , pH 3.5-4.3, and electroplating time is 60-120s.
5. The nickel roughening process for a lead frame according to claim 1, characterized in that: When the thickness of the electroplated rough nickel layer is 1 micron, the surface area of the electroplated rough nickel layer is 1.3-1.5 times the surface area of the corresponding electroplated area of the lead frame.
6. The nickel roughening process for a lead frame according to claim 1, characterized in that: The anode in the electroplating tank is a titanium alloy anode basket filled with sulfur-containing nickel blocks.
7. The nickel roughening process for a lead frame according to claim 1, characterized in that: The electroplating nickel roughening solution also includes: 5-10 g / L of TiO2 / SiO2 nanocomposite particles and 0.3-0.5 g / L of a dispersant.
8. A nickel roughening process for a lead frame according to claim 7, characterized in that: The method for preparing the TiO2 / SiO2 nanocomposite particles comprises the following steps: S81, according to the mass fraction, add 5 parts of nano-TiO2 powder to a solution consisting of 500 parts of anhydrous ethanol and 300 parts of deionized water, stir evenly, add 0.2 parts of polyvinyl pyrrolidone K30, and ultrasonically disperse for 50-60 minutes to obtain a mixed solution A; S82, dripping 100 parts of 40% tetraethyl orthosilicate anhydrous ethanol solution into mixed solution A, completing the dripping within 3 hours, adding ammonia water every 20 minutes during the dripping process, adjusting the pH to 10-10.5, and continuing the reaction for 5-6 hours after the dripping is completed to obtain mixed solution B; S83. Centrifuge the mixed solution B, wash it with pure water for 5 times, dry it in an oven at 120-130°C for 8-10 hours, and grind it to obtain TiO2 / SiO2 nanocomposite particles with a particle size of 20 nanometers.
9. A nickel roughening process for a lead frame according to claim 8, characterized in that: The average particle size of the nano-TiO2 powder is 5 nanometers.
10. The nickel roughening process for a lead frame according to claim 8, characterized in that: The dispersant is composed of sodium dodecylbenzene sulfonate, sodium dodecyl polyoxyethylene ether sulfate and polyethylene glycol octylphenyl ether in a mass ratio of 3:4:3.
Citation Information
Cited By
Nickel plating process and pre-electroplating lead frame
CN120649103A
